Functional analysis of AP2/ERF family members in flavonoid biosynthesis of wolfberry - Li, Ronghui; Xia, Shijia; Long, Qiyuan; Jin, Cheng; Li, Haoxia; Xu, Yuhui; Chen, Yuchao; Gan, Xiaoyan; Zhang, Yuanyuan; Zhao, Jianhua (Frontiers in Plant Science, 2025)
Flavonoids, a group of major bioactive ingredients, contribute to the nutritional and medicinal properties of wolfberry (Lycium barbarum). APETALA2/Ethylene response factors (AP2/ERFs) are widely distributed in plants and play crucial roles in regulating growth, development, and stress responses. However, the knowledge of AP2/ERF genes in wolfberry remains limited, and specific AP2/ERF family members involved in flavonoid biosynthesis have not been identified. Here, we systematically identified and characterized AP2/ERF proteins in wolfberry and identified key AP2/ERF family members involved in regulating flavonoid biosynthesis. LbAP2/ERF genes were identified via BLASTP and HMM analysis, using Arabidopsis AP2/ERF as queries and the L. barbarum genome. Gene duplication was analyzed with DupGen_finder, fruit RNA-seq was tested to determine expression profiles across five developmental stages, and LbAP2/ERF089 function was verified using transient overexpression and dual-luciferase assays. A total of 148 genes belonging to the L. barbarum AP2/ERF (LbAP2/ERF) family were identified, with dispersed duplication likely being the primary driver of their amplification. The LbAP2/ERF genes exhibit distinct expression profiles during different stages of fruit development, indicating their potential importance in wolfberry fruit development. Based on the metabolite and gene network analysis, a series of LbAP2/ERF genes involved in flavonoid biosynthesis were identified, including LbAP2/ERF089, LbAP2/ERF011, LbAP2/ERF068, and LbAP2/ERF099. Functional analysis further revealed that LbAP2/ERF089 positively regulates flavonoid synthesis by activating the expression of biosynthetic genes LbLAR and LbDFR. Overall, our results provide new insights into the transcriptional regulation of flavonoid and anthocyanin biosynthesis and offer valuable genetic resources for enhancing the nutritional and medicinal value of wolfberry.